2009
DOI: 10.1891/1559-4343.11.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Pressures to Practice Unethically: Research and Suggested Strategies

Abstract: Research indicates that school psychologists and special education teachers sometimes face pressures from school administrators to practice unethically. It includes quantitative and qualitative data on: School psychologists' and special education teachers' predictions of their responses to administrative pressures to practice unethically; personal and situational factors related to their predictions; errors in some respondents' ethical reasoning; strategies for responding to pressures to practice unethically; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Empirical research has provided insight into the conflict between best interests of the child and legal or administrative compliance. Specifically, Helton and Ray (2009) introduced the concept of competing loyalties to describe how educators are negatively affected by administrative pressures to act unethically. In their study, educators felt forced to follow administrative directives and to comply with laws and regulations rather than adhere to their personal ethical codes.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has provided insight into the conflict between best interests of the child and legal or administrative compliance. Specifically, Helton and Ray (2009) introduced the concept of competing loyalties to describe how educators are negatively affected by administrative pressures to act unethically. In their study, educators felt forced to follow administrative directives and to comply with laws and regulations rather than adhere to their personal ethical codes.…”
Section: Discussionmentioning
confidence: 99%
“…Fiedler and Van Haren (2009) concluded that school administrators must not only hold "ethical codes of conduct and professional standards" (p. 162) but must also (1) be well-versed in special education and its services in order to make ethical decisions; and (2) reflect an advocacy of concern and commitment in their school communities regarding children with disabilities (p. 172). Helton and Ray (2009) noted four types of special education ethical decisions errors made by school administrators: (1) decisions resulting from administrative pressure to practice unethically; (2) placing one's own beliefs before ethical codes of practice; (3) following administrative directives regardless of practitioner ethical responsibilities; and (4) teachers not receiving support from administrators when a child's special education plan is not being implemented (p. 115 (Sheldon, Angell, Stoner, & Roseland, 2010).…”
Section: Council Of Exceptional Childrenmentioning
confidence: 99%
“…Professionals, according to common standards and guidelines, are expected to continue to learn in their areas of expertise and promote this new learning through action and practice. Often administrators caught in the dilemma of managing a budget and offering specialized educational services might pressure educators to practice unethically (Helton & Ray, 2009). An important aspect of gifted education is the building of ethical decision making (Tirri, 2011).…”
Section: Enhancing Ethical Awarenessmentioning
confidence: 99%